Aplikasi Sistem Informasi Smart Register Online Berbasis Android Menggunakan Algoritma Brute Force - Dimas Dandy Aryarajendra Suprapto; Fauziah Fauziah; Iskandar Fitri; Nur Hayati (Universitas Hamzanwadi, 2020)
The process of registering new students (PMB) for sharing information displayed on the website based PMB information system. However, constraints in the usage of the website are prospective students must monitor the website frequently to obtain information. If not accordingly a student is at risk of lagging behind the latest information. The research aims to expand a registration information system on the enrollment of student-based websites and developed into an Android-based application. So it is very easy for students to access PMB information, and registration through the Android application. This study designed an Android-based registration information system application using the waterfall method, brute force algorithm, integrated realtime firebase database and firebase storage cloud. The results of testing the brute force algorithm on the word search